Classification of kitchen pots from the medieval walled city Dzhankent (Journal of history, 2021)
The main archaeological material found at the site of Dzhankent for 15 years of its study is ceramics. Long-term research of the monument, allowed to obtain a massive ceramic material. To date, the ceram- ics of Jankent are still poorly studied and do not have a complete classification.Dzhankent ceramics are heterogeneous and complex in their composition. According to the manu- facturing method, it is divided into stucco and pottery. Depending on their functional purpose, ceramics are divided into several categories. Categories are classified into smaller units. This article presents the beginning of this classification work.The paper gives a brief description of ceramic kitchen pots from the Dzhankent settlement. This is one of the main types of cooking utensils. The classification of kitchen pots and a brief description of the technology of their manufacture are given. Photo and drawings of ceramics were used in the work.The paper also provides some analogies for the glassware under study. So kitchen pots from the Dzhankent settlement are most similar to materials from the monuments of South Kazakhstan (Otrar, Karatobe).Thus, the classification of ceramic kitchen pots from the Dzhankent settlement is only the beginning. In the future, it is planned to conduct a complete analysis and typology of all categories of ceramics in Dzhankent.Key words: Dzhankent, medieval ceramics, kitchen pots, ceramics classification.